Novel Methodology for the Efficient Synthesis of 3-Aryloxindoles: [1,2]-Phospha-Brook Rearrangement–Palladium-Catalyzed Cross-Coupling Sequence - Kondoh, Azusa; Takei, Akira; Terada, Masahiro (Synlett, 2016)
A novel methodology for the efficient synthesis of 3-aryloxindoles from isatin derivatives was developed. The methodology involves the formation of an oxindole having a phosphate moiety at the C-3 position via the [1,2]-phospha-Brook rearrangement under Brønsted base catalysis followed by palladium-catalyzed cross-coupling with aryl boron reagents. The one-pot synthesis of 3-aryloxindoles from isatin derivatives is also described.
Keywords: oxindole derivatives; phospha-Brook rearrangement; Brønsted base catalysis; cross-coupling; palladium catalyst